Simulation and prediction of changes in tree species composition in subtropical forests of China using a nonlinear difference equation system model - Ji, Biyong; Yu, Kunyong; Wang, Fan; Ge, Hongli; Liu, Jian (Frontiers in Plant Science, 2023)
Changes in tree species composition are one of the key aspects of forest succession. In recent decades, significant changes have occurred in the tree species composition of subtropical forests in China, with a decrease in coniferous trees and an increase in broad-leaved trees. This study focuses on Zhejiang Province, located in the subtropical region of China, and utilizes seven inventories from the National Continuous Forest Inventory (NCFI) System spanning 30 years for modeling and analysis. We categorized tree species into three groups: pine, fir, and broadleaf. We used the proportion of biomass in a sample plot as a measure of the relative abundance of each tree species group. A novel nonlinear difference equation system (NDES) model was proposed. A NDES model was established based on two consecutive survey datasets. A total of six models were established in this study. The results indicated that during the first two re-examination periods (1989)(1990)(1991)(1992)(1993)(1994)(1994)(1995)(1996)(1997)(1998)(1999), there was significant fluctuation in the trend of tree species abundance, with no consistent pattern of change. During the latter four re-examination periods